Between a rock and a hard place: Economic expansion and social responsibility in UK media discourses on the global alcohol industry. (February 2017) - Thornton, Mary; Hawkins, Benjamin
Abstract: Context: Transnational alcohol corporations (TACs) employ a range of strategies to achieve their business objectives, including attempts to frame perceptions of their activities in media debates. TACs aim to achieve a favourable regulatory environment by presenting themselves as socially responsible actors. However, the need to secure financial investment means they must also emphasise their potential for growth. This article investigates tensions between these objectives in coverage of the global alcohol industry in the UK print media. Methods: This article examines coverage of the world's four largest TACs in five British daily newspapers and one industry publication between March 2012 and February 2013. 477 articles were identified for analysis through keyword searches of the LexisNexis database. Thematic coding of articles was conducted using Nvivo software. Findings: Two conflicting framings of the alcohol industry emerge from our analysis. The first presents TACs as socially responsible actors; key partners to government in reducing alcohol-related harms. This is targeted at policy-makers and the public in an attempt to shape policy debates. The second framing highlights TACs' potential for economic growth by establishing new markets and identifying new customer bases. This is targeted at an audience of potential investors. Conclusions: A fundamental contradiction lies at the heart of these framings, reflecting the tensions that exist between TACs' political and financial strategies. Alcohol industry involvement in policy-making thus involves a fundamental conflict of interests. Consequently, the UK government should reassess the prominence it currently affords to the industry in the development and delivery of alcohol policy. Highlights: Contradictory framings of the alcohol industry speak to different audiences. For policy-makers they are framed as socially responsible actors. For potential investors, they highlight their aggressive pursuit of growth. Clear tensions exist between alcohol industry financial and political strategies. Government should view TACS as vested interests, not as partners in policy-making.